+0  
 
0
273
1
avatar

How do you solve -6-3y=27 with work ?

Guest Mar 22, 2017
 #1
avatar+7153 
+2

The main thing you have to remember is whatever you do to one side of the equation, you must do to the other side to keep the equation true.

-6 - 3y = 27

 

Add 6 to both sides. The 6 on the left side goes away when you add 6.

-3y = 27 + 6

 

-3y = 33

 

Divide both sides by -3. The -3 on the left side goes away when you divide by -3.

y = 33/(-3)

 

y = -11         Now it is solved for y. :)

hectictar  Mar 22, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.